2021
DOI: 10.1186/s12889-021-10696-x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and clinical challenges in sexual health care provision to men who have sex with men in Tanzania: a qualitative study of health professionals’ experiences and health students’ perspectives

Abstract: Background Health care providers across sub-Saharan Africa continue to face challenges while delivering sexual health care services. We explored the experiences, views and challenges of health care professionals and health students across different disciplines in Tanzania, towards delivery of sexual health services to men who have sex with men. Methods Utilizing a qualitative approach, we recruited 121 health care professionals (providers) and stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
2
10
0
3
Order By: Relevance
“…Though some HCPs demonstrated knowledge and ability to address the health needs of TSMSM (such as anal STIs), other HCPs indicated they had never "heard of anal STIs in college". The lack of pre-service training on the health needs of non-heterosexual individuals and how to respond to these needs was reported in the current study, and has also been observed in other studies in Kenya, Uganda and Tanzania (47)(48)(49). Evidence from Kenya and South Africa suggests that sensitization and training reduces homo-prejudice and improves knowledge and skills of HCPs (46, [50][51][52], and should hence be considered for adoption and scale-up among HCPs in tertiary academic institution-based health facilities.…”
Section: Discussionsupporting
confidence: 81%
“…Though some HCPs demonstrated knowledge and ability to address the health needs of TSMSM (such as anal STIs), other HCPs indicated they had never "heard of anal STIs in college". The lack of pre-service training on the health needs of non-heterosexual individuals and how to respond to these needs was reported in the current study, and has also been observed in other studies in Kenya, Uganda and Tanzania (47)(48)(49). Evidence from Kenya and South Africa suggests that sensitization and training reduces homo-prejudice and improves knowledge and skills of HCPs (46, [50][51][52], and should hence be considered for adoption and scale-up among HCPs in tertiary academic institution-based health facilities.…”
Section: Discussionsupporting
confidence: 81%
“…As detailed in Table 1 37 , there were 60 experienced healthcare providers, including 11 men and 49 women. Their ages ranged from 24 to 62 years, and had, on average, 15 years of clinical experience.…”
Section: Resultsmentioning
confidence: 99%
“…The methods for this study have been published elsewhere. 37 To summarise, we utilised a stratified three (profession: midwifery, nursing, medicine) by two (experience: clinicians vs students) design. The main objective was to assess and compare how providers address sexual health concerns across professions and by experience (providers vs students) in order to identify curriculum priorities.…”
Section: Methodsmentioning
confidence: 99%
“…Details of study activities have been previously described. 14 Briefly, given the highly stigmatized and criminalized nature of homosexuality in Tanzania at the time of the study and to the present, 15 MSM were recruited using respondent-driven sampling (RDS) which provided access to MSM utilizing established networks of friends and acquaintances. Five initial respondents were contacted in Dar es Salaam and these persons referred up to 3 persons each using study coupons.…”
Section: Methodsmentioning
confidence: 99%